1995
DOI: 10.1161/01.hyp.25.4.790
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Adrenomedullin-Induced Vasodilation in the Rat Kidney

Abstract: To explore the mechanisms of adrenomedullin-induced vasorelaxation, we tested the effects of adrenomedullin on renal function in rats in vivo and measured the release of endothelium-derived nitric oxide from isolated perfused rat kidney (using a chemiluminescence assay) and the diameters of the glomerular arterioles in the hydronephrotic kidney. Adrenomedullin decreased blood pressure in a dose-dependent manner (3 nmol/kg: -29 +/- 2% [SEM]; P < .01) and slightly increased the glomerular filtration rate and uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(110 citation statements)
references
References 29 publications
4
106
0
Order By: Relevance
“…In addition, Jensen et al (1996Jensen et al ( , 1997 have identified by RT-PCR the presence of AM in afferent and efferent arterioles, but not in juxtaglomerular granular cells in culture. They have also confirmed the stimulation of renin release by AM, an event previously reported by Hirata et al (1995).…”
supporting
confidence: 84%
“…In addition, Jensen et al (1996Jensen et al ( , 1997 have identified by RT-PCR the presence of AM in afferent and efferent arterioles, but not in juxtaglomerular granular cells in culture. They have also confirmed the stimulation of renin release by AM, an event previously reported by Hirata et al (1995).…”
supporting
confidence: 84%
“…For example, AM dilates the renal vasculature, and the kidneys show one of the highest levels of expression and secretion of AM (25). AM exhibits diuretic and sodium-excreting effects associated with renal vascular dilation (26,27). On the other hand, in a study by Cheung et al, patients with chronic respiratory disorders and secondary pulmonary hypertension showed an elevation in plasma AM (28).…”
Section: Discussionmentioning
confidence: 99%
“…27 When adrenomedullin was added to the cultures together with 2 mmol/L L-NAME, an inhibitor of NO synthase, the antiapoptotic effect was completely abrogated (Figures 4A and 4B). Furthermore, SNP (10 mol/L), a NO donor, mimicked the antiapoptotic effect of adrenomedullin.…”
Section: Antiapoptotic Effect Of Adrenomedullin Is Mediated By Nomentioning
confidence: 97%